PENGARUH PANJANG SETEK DAN LAMA PERENDAMAN DENGAN ZPT INDOLE BUTYRIC ACID (IBA) TERHADAP PERTUMBUHAN SETEK TANAMAN JERUK LEMON (Citrus limon(L.) Burm.f.) - Wulan Sri Rahayu; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Lemon plant (Citrus limon L. Burm.f.) is a horticultural commodity that is well known by the public as a multipurpose fruit. The length of the cuttings and the long immersion with ZPT can increase the growth of lemon seedlings. This study aims to determine the effect of cutting length and immersion time with ZPT Indole Butyric Acid (IBA) on the growth of citrus limon (L) Burm.f. cuttings and to obtain cutting length and duration of soaking with ZPT Indole Butyric Acid (IBA) to the best growth of lemon cuttings (Citrus limon (L) Burm.f.). This research was conducted at the Experimental Garden at the Faculty of Agriculture, University of Riau, from May to July 2019, using a factorial completely randomized design (CRD) consisting of 2 treatment factors and 3 replications consisting of the first factor is the length of the cuttings consisting of 3 levels ( 10 cm, 15cm, 20cm) The second factor is the length of immersion in the IBA solution which consists of 4 levels (0 hours, 12 hours, 24 hours, 36 hours). The parameters observed were shoot appearance, shoot length, shoot number, shoot diameter, shoot dry weight, and root volume. The data obtained were analyzed statistically by using analysis of variance then continued with the further test of Honestly Significant Difference (BNJ) at 5% level. The combination of 20 cm cutting length and 24 hours immersion resulted in the best shoot length.Keywords: Lemon, Cutting Length, Soaking Time, ZPT, IBA